Are anticorruption conventions human rights treaties? - Novoa Curich, Yvana Lucía (2016)
This article seeks to determine whether international anticorruption conventions can be considered human rights treaties. The conclusion the author arrives to in the present article involves a new approach to understand the effects of the implementation of the aforementioned conventions in Peru.To answer the question whether these conventions are human rights treaties, the author explains the aim and the purpose of these conventions, and addresses its role on democracy and its relation with Human Rights. Finally, the author wonders if it is possible to recognize a fundamental right to a non-corrupt government.